Body condition of females during tadpole attendance and its potential costs in a Neotropical foam-nesting frog (Leptodactylus podicipinus). Issue 2 (4th March 2023) - Cuestas Carrillo, Juan F.; Santana, Diego J.; Prado, Cynthia P.A.
Abstract : Parental care increases offspring survival, but may be costly for parents, reducing future survival and reproduction. Offspring attendance may increase predation risk, or reduce food intake, mating opportunities, and reproductive rate of parents. Anurans exhibit a great diversity of parental care behaviours and offer an opportunity to investigate the costs and benefits of parenting. Here, we measured the body condition of females of the Neotropical frog Leptodactylus podicipinus during tadpole attendance. By comparing attending and non-attending females, we tested the hypothesis that females providing care will have reduced body condition and food ingestion. Although fat body mass did not differ, attending females had significantly lower body mass, ovary mass, and stomach volume after 6 days of care. Overall, attending females may lose up to 40% of body mass due to parental care, while non-attending females gain mass. Although 27% of attending females had empty stomachs, prey diversity was higher. Additionally, the higher proportion of aquatic hemipterans and spiders preyed on by attending females may be explained by different microhabitat use and active protection of offspring. Our results indicate that parental care has the potential to affect future reproduction of females via reduction in body condition and food intake. Studies have shown the benefits related to offspring survival in anurans, but few addressed the costs to parents. By evaluating the potential costs of parenting in a frog species with aquatic tadpoles for the first time, our study contributes to fill this gap. Studies investigating the costs and benefits of parental care in different lineages of frogs will improve our knowledge on the evolution of parenting in this highly diverse group.